Vitamin K catabolite inhibition of ovariectomy‐induced bone loss: Structure–activity relationship considerations. Issue 8 (14th July 2014) - Soper, Robin J.; Oguz, Cenk; Emery, Roger; Pitsillides, Andrew A.; Hodges, Stephen J.; Traber, Maret G.
<x xml:space="preserve">Abstract</x> Scope The potential benefit of vitamin K as a therapeutic in osteoporosis is controversial and the vitamin K regimen being used clinically (45 mg/day) employs doses that are many times higher than required to ensure maximal gamma‐carboxylation of the vitamin K‐dependent bone proteins. We therefore tested the hypothesis that vitamin K catabolites, 5‐carbon (CAN5C) and 7‐carbon carboxylic acid (CAN7C) aliphatic side‐chain derivatives of the naphthoquinone moiety exert an osteotrophic role consistent with the treatment of osteoporosis. Methods and results Osteoblast‐like MG63 cell cultures were challenged with lipopolysaccharide and the levels of interleukin‐6, an osteoclastogenic cytokine, measured with and without catabolites; low concentrations of CAN7C significantly inhibited interleukin‐6 release, but CAN5C did not. In models of bone loss induced by ovariectomy or sciatic neurectomy in C57BL/6 mice, we found that the rarer CAN7C catabolite markedly restricted ovariectomy‐induced bone loss and possibly limited sciatic neurectomy‐induced bone loss. CAN7C activity depends on a free carboxylic acid and its particular side‐chain structure. Conclusion These in vivo data indicate for the first time that the clinical utility of vitamin K for osteoporosis may reside in an unusual catabolite.